IMPLEMENTASI VIEKRITERIJUMSKA KOMPROMISNO RESENJE DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN SISWA BERPRESTASI DI SMP MUHAMMADIYAH KUPANG - Ali Akbar Syah, Arrahim; Sumarlin (Jurnal Publikasi Manajemen Informatika, 2025)
. Determining outstanding students is one of the important aspects in the world of education that aims to provide awards to students who have shown excellence in various fields. This process is usually carried out based on various criteria that include academic achievement, activeness in extracurricular activities, attitudes and behaviors, and leadership skills. This study aims to implement the VIKOR method in determining outstanding students. Decision Support Systems (DSS) are information technology-based systems designed to assist the decision-making process in situations involving various factors or criteria. The VIKOR method (VlseKriterijumska Optimizacija I Kompromisno Resenje in Serbian, which means Multicriteria Optimization and Compromise Solution) is a ranking method using a multicriteria ranking index based on a certain measure of proximity to the ideal solution.